Ethical issues in topical computer vision applications - Lauronen, Mikael (2017)
Computer vision is a research area that contains multiple methods to approach numerous visual problems. In the past decade, it has been rapidly evolving with the introduction of many new technologies and applications that utilize different computer vision techniques. The purpose of this study is to identify the ethical issues that concern recent trending computer vision applications and their tasks. This was done by conducting an integrative literature review and synthesizing various studies that have been conducted on the different applications of computer vision and their ethical issues. The result was a synthesized framework of different ethics themes that relate to the different areas of computer vision. The results were presented in a written and visual representation of the current knowledge on the topic. It was made sure that the study is valid and reliable. Six categories of different ethical issues were recognized, which are espionage, identity theft, malicious attacks, copyright infringement, discrimination and misinformation. Based on the findings, a discussion was conducted to point out the several gaps that exists in the current research area of computer vision and its ethical issues. Further research on the topic was encouraged.